Gender Difference in Associations Between Telomere Length and Risk Factors in Patients With Stroke - Wang, Yuqing; Jiao, Fengjuan; Zheng, Huancheng; Kong, Qingsheng; Li, Ran; Zhang, Xiaojie; Yan, Li; Hao, Yanlei; Wu, Yili (Frontiers in Aging Neuroscience, 2021)
Multiple risk factors of stroke are associated with telomere length shortening. Although leukocyte telomere length (LTL) is shorter in patients with stroke, the heterogeneity is high. Risk factors may be differentially associated with LTL in male and female patients contributing to the heterogeneity. However, the gender difference in associations between LTL and risk factors in stroke patients has not been investigated. In this study, we investigated the gender difference in associations between LTL and risk factors in 312 stroke patients. Real-time quantitative PCR was used to determine relative LTL, and multiple linear regression analysis was applied for association analyses. We found that LTL was negatively associated with triglyceride (TG) in all patients [β(95% CI) = −0.69 (−1.26, −0.11), P < 0.05] after adjusting confounders. Importantly, LTL was negatively associated with lack of exercise [β(95% CI) = −1.80 (−3.12, −0.49), P < 0.05] and LDL levels [β(95% CI) = −3.22 (−6.05, −0.390), P < 0.05] in male patients, while LTL was negatively associated with dyssomnia [β(95%CI) = −2.00 (−3.96, −0.07), P < 0.05] and diabetes [β(95%CI) = −2.13 (−4.10, −0.27), P < 0.01] in female patients. Our study showed that LTL is differently associated with risk factors in male and female patients with stroke, indicating that gender difference should be considered when LTL is potentially applied as an index of risk and prognosis for stroke. Our study also provides an insight into that gender differences should be considered when developing intervention strategies for stroke prevention and treatment.